The Tilawati Method in Qur'an Learning at the Nahdhatul Quran Tahfizh House, Manarap Village, Danau Panggang District - Hasna ‘Afifah; Ria Susanti; Mahmud (Integrated Education Journal, 2026)
Learning motivation is a key factor in the success of the educational process, especially in learning the Quran. Students who have high motivation will be more enthusiastic in learning and understanding the material and will be more consistent in reading and memorizing the Quran. Conversely, a lack of motivation can hinder the development of students' abilities in mastering the knowledge of the Quran. Therefore, effective learning methods are needed to motivate students to learn so that they are more enthusiastic and diligent in learning. This study aims to describe how the use of the Tilawati method in learning the Quran to motivate students to learn, including: the steps in its implementation, the strategies of the female teachers in motivating students to learn, and the success of the Tilawati method in motivating students to learn. The research location was at the Nahdhatul Quran Quran Memorization House in Manarap Village, Danau Panggang District, Hulu Sungai Utara Regency. This study used a descriptive qualitative approach. The subjects were six Quran teachers and three female students, while the informants consisted of the caretaker of the Nahdhatul Quran Islamic boarding school, the head/coordinator of the RTQ, and the RTQ administrators. Data collection was conducted using observation, interviews, and documentation techniques. The research results show that Quranic learning based on the Tilawati method meets the standards for systematic and effective learning, encompassing planning, implementation, and evaluation. The strategies implemented by the female teacher include a personal approach, appreciation methods, interactive learning, a conducive learning environment, the use of props and Rost rhythm, and a U-shaped seating arrangement, all of which have been shown to increase the motivation of female students. Positive outcomes/impacts of this method include increased enthusiasm, discipline, self-confidence, independence and active learning, the quality of Quranic recitation, and a better learning environment.